2010
DOI: 10.1143/jjap.49.07he22
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Liquid in a Long Pore Opened at Both Ends Using High-Intensity Aerial Ultrasonic Waves

Abstract: We experimentally verified a method by which a liquid that has entered a long pore with open ends can be removed from the pore by using the acoustic radiation force produced by high-intensity aerial ultrasonic waves at a frequency of 20 kHz. The intensity of the ultrasonic waves was about 6 to 10 kPa. By using this method, it was confirmed that a liquid in pores of 1.5 to 5.0 mm diameter and 3 to 20 mm length could be instantaneously removed from the pores. This method, which did not use any air flow at a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…[12][13][14] Ito et al reported the generation of strong aerial ultrasonic waves of 15 kPa as an estimated value in a point-converging source consisting of a deflection diaphragm connected to a BLT and a rotating parabolic reflector. 15) High-intensity airborne ultrasound is used for many applications such as surface cleaning, 16) atomization, 17,18) liquid removal, [19][20][21] gas removal, 22) non-contact excitation, 23) internal defect detection, 24,25) damage detection, 26,27) surface monitoring, 28) impregnation, 29) drying, 30) and agglomeration. 31) On the other hand, a different approach is the idea of using powerful laser ultrasound as an airborne ultrasonic source with high intensity and small size.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Ito et al reported the generation of strong aerial ultrasonic waves of 15 kPa as an estimated value in a point-converging source consisting of a deflection diaphragm connected to a BLT and a rotating parabolic reflector. 15) High-intensity airborne ultrasound is used for many applications such as surface cleaning, 16) atomization, 17,18) liquid removal, [19][20][21] gas removal, 22) non-contact excitation, 23) internal defect detection, 24,25) damage detection, 26,27) surface monitoring, 28) impregnation, 29) drying, 30) and agglomeration. 31) On the other hand, a different approach is the idea of using powerful laser ultrasound as an airborne ultrasonic source with high intensity and small size.…”
Section: Introductionmentioning
confidence: 99%
“…Several technologies that employ these phenomena have been developed. The irradiated high-intensity aerial ultrasonic waves can be used to instantaneously atomize and remove a liquid that has entered a narrow channel or void [11][12][13]. If this becomes practically possible, a cleaning liquid, for example, that leaks into a narrow gap or channel on a circuit board on which electronic devices are mounted or on a precision machine part can be expected to be removed with ease.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] For the cleaning process in the manufacture of machinery and equipment, some cleaning methods have already been developed in which cleaning liquid that had entered into pores and narrow voids could be removed by the acoustic radiation force of aerial ultrasonic waves. [12][13][14][15] Also, some cleaning methods have been realized in which fine grains sticking to the surfaces of objects could be removed by irradiating them with aerial ultrasonic waves in a noncontact and instantaneous way. 16) Recently, we developed a new method of aerial ultrasonic inspection that uses high-intensity aerial ultrasonic waves.…”
Section: Introductionmentioning
confidence: 99%